Facile Preparation of the Synthon of 7-Ethyl-8-oxabicyclo[4.3.0]nonane-2,9-dione - Fang, Li-Zhen; Li, Yong-Hai; Liu, Jing-Ping; Yan, Fu-Lin (Asian Journal of Chemistry, 2011)
The useful synthon of 7-ethyl-8-oxabicyclo[4.3.0]2,9-dioxononane was readily synthesized by a facile method. Starting from ethyl-1-bromo-2-oxocyclohexane- carboxylate, the 7-ethyl-8- oxabicyclo[4.3.0]nonane-2,9-dione was obtained by subsequent reactions of elimination, addition and reduction in total 49.4% yield. It showed no significant cytotoxicity to Bel7402 in the preliminary cytotoxicity assay study.